The oldest known basal tiphiid wasp (Hymenoptera, Tiphiidae) from mid-Cretaceous Burmese amber of northern Myanmar. (December 2022) - Zheng, Yan; Zhuo, De; Hu, Haiyan; Chen, Jun; Zhang, Qi; Zhang, Haiguang; Zhang, Haichun; Rasnitsyn, Alexandr P.
Abstract: A new genus and species of tiphiid wasps, Burmatiphia mandibulata gen. et sp. nov., is described and illustrated based on a new specimen from the lowermost Cenomanian Burmese amber as forming a distinct subfamily Burmatiphiinae subfam. nov. The new taxon is characteristic of a combination of striking plesiomorphies (metasomal sterna 1 and 2 forming even surface, female metasomal apical tergum and sternum unmodified with narrow orifice for sting, and female mid and hind tibiae lacking digging adaptation) and synapomorphies (single mid and hind tibial spurs, long and sharp tibial spines, scape with long radix, possibly reduced costal space in fore wing). Burmatiphia gen nov. supposedly hunted for prey within underground tunnels.